Probiotic properties of Bacillus strains isolated from the gastrointestinal tract against pathogenic Vibriosis - Jlidi, Mouna; Akremi, Ismahen; Ibrahim, Adel Haj; Brabra, Wided; Ali, Manel Ben; Ali, Mamdouh Ben (Frontiers in Marine Science, 2022)
Vibriosis is one of the major diseases leading to massive fish mortality. Probiotics may provide a potential alternative method to protect fish from pathogens and to promote a balanced environment minimizing the use of antibiotics and chemotherapy. The aims of this study were to (i) isolate and purify marine spore-former strains from Sardine and shrimp intestine, (ii) screen for bacteria with potential probiotic properties, and (iii) carry out their in vitro safety assessment using a subtractive procedure. Among 108 spore-former strains, five strains exhibited a strong antibacterial activity against Vibriosis such as Vibrio harveyi and Vibrio anguillarum. These selected strains were unaffected by high-temperature and gastrointestinal conditions; produced amylase, protease, and lipase activities; and showed high percentages of auto-aggregation and co-aggregation with pathogens, as well as a strong adhesion to fish mucus. Partial 16S rDNA gene sequencing and MALDI-TOF MS revealed that isolates are Bacillus amyloliquefaciens or Bacillus subtilis. All of them were susceptible to antibiotics, while hydrolic enzymes and virulence factors were not detected for B. subtilis S17. In conclusion, based on their proprieties and their safety assessment, B. subtilis S17 could serve as a potential probiotic candidate for aquaculture.